Estudos sobre a nutrição mineral do cafeeiro: XXXI. influêcia do cobre do substrato no crescimento e composição mineral do cafeeiro (Coffea arabica L.) variedades Mundo Novo e Catuaí - Andrade, V. M. de [UNESP]; Lourenço, R. S.; Muraoka, T.; Malavolta, E. (Universidade de São Paulo (USP), Escola Superior de Agricultura, 1976)
Foi estudado o efeito do cobre do substrato no crescimento, sintomatologia e composição mineral do cafeeiro novo. Verificou-se ser a var. Mundo Novo mais sensível à toxidez do cobre por translocar maior proporção do elemento que a var. Catuaí. O uso de calcário e de matéria orgânica no solo neutraliza o sobre tóxico.

This work was designed to study the effect of copper in the medium on growth and mineral composition of the coffee plant, bearing in mind the possibility of accumulation of toxic residues in the soil as a consequence of the treatments against rust. Young plants of the varieties Mundo Novo and Catuái were grown in nutrient solution in the presence of Cu concentrations from 0.02 to 200 ppm. Toxic effects were found to be darkening and cessation of root growth; wilt, necrosis and leaf drop; abnormalities in the epidermis, parenchyma and chlorophasts. The threshold level for copper toxicity is around 30 ppm in the leaves. Mundo Novo seems to be more sensitive to copper toxicity. Under soil conditions it was found that the joint use of lime and stable manure eliminates the toxicity of an application of 200 ppm of cooper.
Studies on the mineral nutrition of the coffee plant: XXXI. influence of copper in the substrate on growth and mineral composition of the coffee plant varieties Mundo Novo and Catuaí